Identifying the optimal level of gold as a reserve asset using Black–Litterman model: The case for Malaysia, Turkey, KSA and Pakistan. Issue 3 (2nd March 2018) - Bayram, Kamola; Abdullah, Adam; Meera, Ahamed Kameel
Abstract : Purpose: After the collapse of the Bretton Woods fixed exchange rate system in 1971, countries moved towards floating exchange rates, and the expectation was that the requirement for foreign reserves would decrease. However, central banks currently hold more foreign exchange reserves to enhance the credibility of exchange rate policies. The demand for gold, which was the main reserve asset prior the collapse of the Bretton Woods system, has increased as a reserve asset once again following the global financial crisis (GFC) of 2008, given gold's characteristics as a safe haven asset and a store of value. This study aims to analyse official reserves of four countries, namely, Malaysia, Turkey, KSA and Pakistan. The Black–Litterman model was used to build a new strategic portfolio with optimal allocation to gold. This study shows that all countries under the analyses should increase their gold holdings to preserve the value of the portfolio during times of financial turmoil. Design/methodology/approach: The Black–Litterman model has been used to build a new strategic portfolio with optimal allocation to gold. The study shows that all countries in our analyses suggested increasing their gold holdings to preserve the value of the portfolio during times of financial turmoil. Findings: The study found that countries under the analyses, namely, Turkey, Malaysia, KSA and Pakistan, suggested increasing their official gold holding given the outstanding performance of gold during the GFC. Research limitations/implications: Research can be further extended by including few more countries from Organisation of Islamic Cooperation such as Qatar and Indonesia. Originality/value: Emerging economies such as China, India and Russia started to sharply increase their official gold holdings in the aftermath of the GFC. According to recent statistics, central banks of China and Russia have been adding to their gold reserves. Of note, only in few European countries and in the USA, is the share of gold in foreign reserves more than 50%. In the rest of the world, this figure is about 3-5%. The paper elaborates the aforementioned subject and suggests the strategic weight of gold reserve for each country under analysis.